Cavities create a potential back door in epoxide hydrolase Rv1938 from Mycobacterium tuberculosis—A molecular dynamics simulation study. (October 2015) - Selvan, Anitha; Anishetty, Sharmila
Graphical abstract: Highlights: MD simulation of epoxide hydrolase, Rv1938 from Mtb was carried out for 100 ns. Additional new cavities apart from the substrate binding pocket have been identified. These cavities which are located behind the active site may behave as a backdoor. Cavities may have a role in product exit. Cavity1 may possibly aid in water access to the active site. Abstract: Mycobacterium tuberculosis (Mtb) is the causative organism of tuberculosis. Extensively drug resistant strains and latency have posed formidable challenges in the treatment of tuberculosis. The current study addresses an alpha/beta hydrolase fold bearing enzyme, epoxide hydrolase Rv1938 from Mtb. Epoxide hydrolases are involved in detoxification processes, catabolism and regulation of signaling molecules. Using GROMACS, a 100 ns Molecular Dynamics (MD) simulation was performed for Rv1938. Cavities were identified within the protein at various time frames of the simulation and their volumes were computed. During MD simulation, in addition to the substrate binding cavity, opening of two new cavities located behind the active site was observed. These cavities may be similar to the backdoor proposed for acetylcholinesterase. Structural superimposition of epoxide hydrolase from Mtb with the epoxide hydrolase of Agrobacterium radiobacter1 AD1 (Ephy) indicates that cavity1 in Mtb lies at an identical position to that of the water tunnel in Ephy. Further, docking of the substrate and an inhibitor with protein structures obtained from MD simulation at various time frames was also performed. The potential role of these cavities is discussed.